Rheological aspects in fabricating pullulan-whey protein isolate emulsion suitable for electrospraying: Application in improving β-carotene stability. (July 2020) - Niu, Ben; Shao, Ping; Feng, Simin; Qiu, Dan; Sun, Peilong
Abstract: Beta-carotene has been used as a food colorant and functional ingredient, but these applications are limited due to its poor stability. The aim of this work was to improve the stability of β-carotene by encapsulating it in electrosprayed particles. The electrohydrodynamic behavior of pullulan solution was studied and the influence of encapsulation and core-to-wall ratio on the stability of β-carotene at different temperatures and relative humidity were investigated. The specific viscosity of the polymer solution increased linearly with the concentration until 5% w/w concentration. The critical entanglement concentration of the pullulan was found to be 4.58% wt. Among the various concentrations of pullulan studied, 3% w/w pullulan solution yielded spherical, monodisperse nanoparticles. Electrosprayed particles with 1:50 core-to-wall ratio had highest encapsulation efficiency. The rate of β-carotene loss displayed first order reaction kinetic within 14 days, while displayed diffusion limited mode after 14 days storage. The retention of β-carotene from the electrosprayed particles accelerated markedly with decreasing temperatures and relative humidity. This study provides a strategy for the preparation of promising electrosprayed particles to improve the stability of β-carotene. Highlights: β-Carotene was encapsulated within pullulan-WPI particles by electrospraying. The electrospraying ability of pullulan dispersions correlated with their viscosity. The β-carotene loss rate first displayed first-order reaction kinetics, then a diffusion-limited mode.